Visualizing the architectures and interactions of nuclear receptors - Khorasanizadeh, S; Rastinejad, F (Oxford University Press, 2016)
Nuclear receptors (NRs) are master regulators of broad genetic programs in metazoans. These programs are regulated in part by the small-molecule ligands that bind NRs and modulate their interactions with transcriptional coregulatory factors. X-ray crystallography is now delivering more complete pictures of how the multidomain architectures of NR homo- and heterodimers are physically arranged on their DNA elements and how ligands and coactivator peptides act through these complexes. Complementary studies are also pointing to a variety of novel mechanisms by which NRs access their DNA-response elements within chromatin. Here, we review the new structural advances together with proteomic discoveries that shape our understanding of how NRs form a variety of functional interactions with collaborating factors in chromatin.